KEBERHASILAN PENANGKAPAN TIKUS (TRAP SUCCESS) DAN INDEKS PINJAL DI DESA KAYUKEBEK KABUPATEN PASURUAN TAHUN 2016 - Ahmad Khoirul Amalul Mutaqin; Ngadino .; Imam Thohari (Poltekkes Kemenkes Surabaya, 2016)
Plague suspect and high flea index is potential transmission of pes. Therefore, it is necessary to conduct rodent and flea observation as an attempt of awareness early occurrence of Extraordinary Events. The purpose of this study was to determine the trap success of flea index. This is a descriptive study by using survey method with cross sectional approach. The study was conducted in Surorowo hamlet, Kayukebek village, Tutur sub district, Pasuruan in February to June 2016. The result showed 29 rats were trapped. The rats found were 17 Rattus tanezumi, 11 Rattus Rattus exulans and one niviventer.The fleas trapped were 17 Xenopsylla cheopis and 3 Stivalius cognatus. 5.67% trap success was carried out in homes, 3.67% in gardens and 0.25% in jungles. Public fleasindex was 0.68; Special flea index of Xenopsylla cheopis was 0.58. From the results above, most of the rats trapped was from Rattus tanezumi type, most trapped fleas was from Xenopsylla cheopis type. Trap success inside and outside homes was categorized as low. Common fleas Index and specific flea index of Xenopsylla cheopis was below standard. There is a need for the provision of number on the trap, increasing the number of traps and training rats catchers. The community is expected to perform trapping independently by providing mousetrap on their own, saving crops in a closed place and providing a closed trash can. Further research on various types of bait can be carried out to know the type of bait rats like. Keywords : trap success and flea index